Evidence of Ventricular Arrhythmogenicity and Cardiac Sympathetic Hyperinnervation in Early Cirrhotic Cardiomyopathy - Liu, Shin-Huei; Lo, Li-Wei; Chou, Yu-Hui; Lin, Wei-Lun; Tsai, Tsung-Ying; Cheng, Wen-Han; Lin, Yenn-Jiang; Chang, Shih-Lin; Hu, Yu-Feng; Chung, Fa-Po; Huang, Hui-Chun; Chen, Shih-Ann (Frontiers in Physiology, 2021)
Cirrhotic cardiomyopathy (CMP) is associated with altered cardiac electrophysiology (EP) properties, which leads to the risk of ventricular arrhythmias (VA). We aimed to evaluate the EP properties, autonomic, and structural remodeling in a rabbit model with early liver cirrhosis (LC). Twelve rabbits were assigned to the sham and LC groups. The early-stage LC was induced by common bile duct ligation. All rabbits received EP study, VA inducibility test, myocardial, and liver histology staining. Western blot analyses of protein expression and tyrosine hydroxylase stain for sympathetic nerves were performed. The effective refractory period the LC group was significantly longer than the sham group (left ventricle 205.56 ± 40.30 vs. 131.36 ± 7.94 ms; right ventricle 206.78 ± 33.07 vs. 136.79 ± 15.15 ms; left atrium 140.56 ± 28.75 vs. 67.71 ± 14.29 ms; right atrium 133.78 ± 40.58 vs. 65.43 ± 19.49 ms, all p<0.01), respectively. The VA inducibility was elevated in the LC group when compared with the sham group (21.53 ± 7.71 vs. 7.8 ± 2.4%, p=0.013). Sympathetic innervation (102 /µm2/mm2) was increased in all cardiac chambers of the LC group compared with the sham group (LV 9.11 ± 4.86 vs. 0.17 ± 0.15, p<0.01; RV 4.36 ± 4.95 vs. 0.18 ± 0.12, p=0.026; LA 6.79 ± 1.02 vs. 0.44 ± 0.20, p=0.018; RA 15.18 ± 5.12 vs. 0.10 ± 0.07, p=0.014), respectively. Early LC is presented with increased ventricular vulnerability, structural heterogeneity, and sympathetic innervation. Close monitoring for fatal arrhythmias is warranted in patients with early stages of LC.